Novel Associations of BST1 and LAMP3 With REM Sleep Behavior Disorder. (9th March 2021) - Mufti, Kheireddin; Yu, Eric; Rudakou, Uladzislau; Krohn, Lynne; Ruskey, Jennifer A.; Asayesh, Farnaz; Laurent, Sandra B.; Spiegelman, Dan; Arnulf, Isabelle; Hu, Michele T.M.; Montplaisir, Jacques Y.; Gagnon, Jean-François; et al.
Abstract : Objective: To examine the role of genes identified through genome-wide association studies (GWASs) of Parkinson disease (PD) in the risk of isolated REM sleep behavior disorder (iRBD). Methods: We fully sequenced 25 genes previously identified in GWASs of PD in a total of 1, 039 patients with iRBD and 1, 852 controls. The role of rare heterozygous variants in these genes was examined with burden tests. The contribution of biallelic variants was further tested. To examine the potential effect of rare nonsynonymous BST1 variants on the protein structure, we performed in silico structural analysis. Finally, we examined the association of common variants using logistic regression adjusted for age and sex. Results: We found an association between rare heterozygous nonsynonymous variants in BST1 and iRBD ( p = 0.0003 at coverage >50× and 0.0004 at >30×), driven mainly by 3 nonsynonymous variants (p.V85M, p.I101V, and p.V272M) found in 22 (1.2%) controls vs 2 (0.2%) patients. All 3 variants seem to be loss-of-function variants with a potential effect on the protein structure and stability. Rare noncoding heterozygous variants in LAMP3 were also associated with iRBD ( p = 0.0006 at >30×). We found no association between rare heterozygous variants in the rest of genes and iRBD. Several carriers of biallelic variants were identified, yet there was no overrepresentation in iRBD. Conclusion: Our results suggest that rare coding variants in BST1 and rare noncoding variants in LAMP3 are associated with iRBD. Additional studies are required to replicate these results and to examine whether loss of function of BST1 could be a therapeutic target.